A STUDY ON ACADEMIC ACHIEVEMENT AND SOCIAL ADJUSTMENT OF HIGH SCHOOL STUDENTS - G.E, Byrasiddappa (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The present study intended to investigate the correlation and difference between academic achievement and Social adjustment of 9th standard students. The Investigator has implemented survey method in view of realizing the objectives of the study Researcher randomly selected a high school as sample and conducted test by using a tool on social adjustment developed by R.C.Deva sample students annual Examination results was considered as academic achievement. The present study sounds that there is a significant difference and relation in the mean score of social adjustment and academic achievement in the high school students with regard to Gender, medium of instruction and students background.